The Canso Causeway:: Tartan Tourism, Industrial Development, and the Promise of Progress for Cape Breton - Beaton, Meaghan; Muise, Del (Acadiensis, 2008)
Abstract This article assesses the conceptualization, construction, and mythologizing of the Canso Causeway, a major post-Second World War reconstruction project that joined mainland Nova Scotia to Cape Breton Island in 1955. Sought after in order to help improve the waning prospects of Cape Breton’s coal and steel industries, the causeway also had a tremendous impact on increasing tourism as a viable industry based on Cape Breton as a traditional but accessible Scottish community. Both tourism and industrial expansion were closely tied to and benefited from a significant policy shift as the federal government began to assume a more interventionist role in regional economic development planning.